Arctic Environmental Test of Survey, Surveillance and Target Acquisition Systems. - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1970)
The report describes test methods and techniques for evaluating the performance and characteristics of Survey, Surveillance and Target Acquisition Systems under arctic winter conditions. The evaluation is related to criteria expressed in applicable Qualitative Materiel Requirements (QMR), Small Development Requirements (SDR), Technical Characteristics (TC), or other appropriate documentation establishing requirements and specifications. (Author)